The Social Life of Information - Lea Wade (Issues in Science and Technology Librarianship)
The article reviews The Social Life of Information. Boston, MA: Harvard Business School Press, 2000. 320 pp. ISBN 0-87584-762-5 by John Seely Brown and Paul Duguid.